2016
DOI: 10.2138/am-2016-5738ccby
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale three-dimensional characterization of iron particles in dusty olivine: Implications for paleomagnetism of chondritic meteorites

Abstract: Dusty olivine (olivine containing multiple sub-micrometer inclusions of metallic iron) in chondritic meteorites is considered an ideal carrier of paleomagnetic remanence, capable of maintaining a faithful record of pre-accretionary magnetization acquired during chondrule formation. Here we show how the magnetic architecture of a single dusty olivine grain from the Semarkona LL3.0 ordinary chondrite meteorite can be fully characterized in three dimensions, using a combination of focused ion beam nanotomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 38 publications
4
51
0
Order By: Relevance
“…Vortex cores in these larger particles develop “winged” structures that protrude along directions in which domain walls nucleate (Figures c and d). Some multivortex scenarios simulated by Einsle et al () are similar to electron holograms in Figure and to the complex magnetization structures documented by Donnelly et al (). The presence of both multiple vortex cores and domain walls in larger particles suggests that the vortex to MD transition is gradual.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Vortex cores in these larger particles develop “winged” structures that protrude along directions in which domain walls nucleate (Figures c and d). Some multivortex scenarios simulated by Einsle et al () are similar to electron holograms in Figure and to the complex magnetization structures documented by Donnelly et al (). The presence of both multiple vortex cores and domain walls in larger particles suggests that the vortex to MD transition is gradual.…”
Section: Discussionsupporting
confidence: 75%
“…Thus, some aspects of the early domain imbalance moment explanation for PSD behavior (Dunlop, ; Shcherbakov, ; Stacey, ) could contribute to developing a more detailed understanding of the full range of magnetic behaviors in the vortex state. Overall, Einsle et al () concluded that particles in the single vortex state with high coercivity and large volume can have long‐term paleomagnetic stability and can be reliable paleomagnetic recorders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations